The Application Degree of Administrative Accountability and Organizational Governance, and the Relationship between them in the Directorates of Education in Jordan from the VieWpoint of its Administrative Leaders - Abdulsalam M. Hatamleh; Kayed M. Salameh (Sultan Qaboos University, 2017)
This study aimed to identify the application degree of administrative accountability and organizational governance, and the relationship between them in the directorates of education in Jordan from the viewpoint of its adm nistrative leaders. The researchers used descriptive statistics- correlation through two tools. A survey for administrative accountability and consisted of -20- items, while the second survey was for organizational governance, it consisted of 40 items concerned with five areas, which are: Revelation and transparency, effective participation, control and administrative responsibility, justice and integrity, and efficiency and effectiveness. The sample consisted of 272 educational leaders from 6 directorates. This represents 14% of the sample community. The results showed that the application degree of administrative accountability and organizational governance in the directorates of education in Jordan was moderate. The results also indicated that there was a significant positive relationship between the application degree of administrative accountability and the application of administrative governance in the directorates of education.